ACCOUNTABILITY FOR VILLAGE FUND MANAGEMENT IN KADING VILLAGE, TANETE RIAJA DISTRICT, BARRU REGENCY. - Jumria; Rosdiana; Rais, Rahmi (Meraja journal, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal